Penerapan Metode Analytical Hierarchy Process pada Kasus Kenaikan Golongan Karyawan Unit Kebun Marjandi - Eka Irawan (LPPM STIKOM Tunas Bangsa, 2019)
The purpose of this research is to analyze with the Analytical Hierarchy Process method, whether the increase in employee class at the Unit Kebun Marjandi can be applied. The results obtained using either manual or computerized calculations show the same results, namely alternative A1 selected as the best alternative in determining the increase in employee class at the Unit Kebun Marjandi. The results obtained in the form of ranking a number of alternative candidates with several criteria as parameters in determining the increase in employee class at the Unit Kebun Marjandi.